Evaluation the Genotoxicity of PHB Nanoparticle by Micronucleus Assay - Jenan A.Ghafil; May. T. Flieh (Indian Journal of Forensic Medicine & Toxicology, 2021)
Determining the toxicity of substances in vivo is one of the most important tests that judge whether ornot they are used in the pharmaceutical field. In the present study, the genetic toxicity of treatment dosesof Polyhydroxybutyrate (PHB), PHB nanoparticles, Cefotaxime and complex of PHB nanoparticlesandcefotaxime was evaluated. The effect of these substances on the number and percentage of white bloodcells (WBCs) in mice was also tested (in vivo). Micronucleus assay was used to assess genotoxicity ofabove materials in vivo, as well as the technique of WBCs chamber was used to estimate the total numberof WBCs in mice administrated with above substances. The differential count of WBCs was measuredby staining the smears with leishman stain. The present study demonstrated that there were no significantdifferences (P>0.05) in the number of micronucleus cells in the mice injected with treatment doses of PHBnanoparticles, Cefotaxime and complex of PHB nanoparticlesand cefotaximewhen compared with miceinjected with normal saline. Similar finding was obtained in terms of counting of total WBCs and differentialcount in mice injected with treatment doses of PHB, PHB nanoparticles, Cefotaxime and complex of PHBnanoparticlesand cefotaxime when compared with WBCs total count and differential count in mice injectedwith normal saline (P>0.05). It can be concluded that there is no toxic effect of treatment doses of PHB, PHBnanoparticles, Cefotaxime and complex of PHB nanoparticlesand cefotaxime on mice.